2015
DOI: 10.5617/nordina.878
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding open inquiry: How a teacher provides students with structure and space

Abstract: The present case study examines a teacher's scaffolding strategies supporting his students during a twelve-week open inquiry project at an upper secondary school. We use interaction analysis to identify how he provides structure and space in the different phases of open inquiry as well as how it constitutes the students' inquiry process. The study reveals that the teacher scaffolded this open inquiry in two opposing ways; he created space for the students to make their own experiences and ideas, which eventual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 20 publications
0
20
0
13
Order By: Relevance
“…- What is already known about the subject which could help to improve the research question and to think about the possibilities of measures? Lehrer and Schauble ( 2002 , 2004 ) Chin and Kayalvizhi ( 2002 ) Bjønness and Kolstø ( 2015 ) T2 (measures → data set) - How will the data be collected? What instruments and/or techniques will be used?…”
Section: What Do Data-texts Look Like In Practice: a Classroom-based Examplementioning
confidence: 99%
See 1 more Smart Citation
“…- What is already known about the subject which could help to improve the research question and to think about the possibilities of measures? Lehrer and Schauble ( 2002 , 2004 ) Chin and Kayalvizhi ( 2002 ) Bjønness and Kolstø ( 2015 ) T2 (measures → data set) - How will the data be collected? What instruments and/or techniques will be used?…”
Section: What Do Data-texts Look Like In Practice: a Classroom-based Examplementioning
confidence: 99%
“…- How many data will be collected? Lehrer and Schauble ( 2002 , 2004 ) Wu and Krajcik ( 2006 ) Bjønness and Kolstø ( 2015 ) Crujeiras-Pérez and Jiménez-Aleixandre ( 2017a ) Crujeiras-Pérez and Jiménez-Aleixandre ( 2017b ) T3 (data → evidence) - Are there any other data that could be more informative? - How will the data be analyzed (statistically, graphically, qualitatively)?…”
Section: What Do Data-texts Look Like In Practice: a Classroom-based Examplementioning
confidence: 99%
“…Det var et stort spenn i utforskning både tematisk og metodisk, for eksempel: «Hvordan virker solarium på produksjon av D-vitamin i personer med ulik hudfarge?» og «Hva er sunnest av flaskevann og vann fra springen?». Elevenes prosjekter ble presentert på en felles utstilling på skolen der over 100 elever deltok (for mer om prosjektet se Bjønness & Kolstø, 2015).…”
Section: Aksjonsforskningsprosjektet Ved Dale Videregående Skoleunclassified
“…After the introduction, the students worked independently in groups of 3-5 persons whilst being guided by the teacher. Their work followed roughly the phases: developing ideas, formulating research question and making a research design, experimenting and discussing, presenting of posters and writing of a report (for more details see Bjønness & Kolstø, 2015). The students' choices of research problems were often close to their interests or daily life, e.g.…”
Section: Background Context Of the 12-week Open Inquiry Projectmentioning
confidence: 99%
“…We worked especially closely with an experienced teacher, Amir, which had implemented open inquiry for students to learn about scientific inquiry and NOS for several years. In the first cycle of the action research, we observed and analysed the open inquiry and found that it represented a simplified version of scientific inquiry, characterized by a step-by-step method and little use of theory to inform the students' inquiries (Bjøn-ness & Kolstø, 2015). In the two next cycles of action research Amir decided to make chances towards a version of open inquiry reflecting a more contemporary view on scientific inquiry, but in the rough and tumble of practice, he fell back on the known practice.…”
Section: Introductionmentioning
confidence: 99%